Beyond temporary migration: Exploring the work values of ex-Indonesian workers through the work and holiday visa program - Indraswari, Candra (INSPIRA: Indonesian Journal of Psychological Research, 2025)
The Work and Holiday Visa (WHV) program offers young people an opportunity not only to travel but also to engage in temporary overseas employment amid increasing youth mobility in Indonesia. As well as a bilateral agreement between the governments of Indonesia and Australia, the WHV program aims to promote cultural exchange at both national and individual levels. However, participation in the program is far from straightforward. Applicants are required to meet strict eligibility criteria and demonstrate financial readiness to sustain themselves while seeking employment in Australia. These challenges make the WHV experience a significant context for the development and transformation of work values among participants. This study aims to explore the work values of former Indonesian Work and Holiday Makers during their stay in Australia and to understand the values they gained after completing the program and returning to Indonesia. Using a qualitative phenomenological approach, this research seeks to capture the lived experiences and the essence of work values shaped through temporary labor migration. Data were collected through in-depth interviews with four former Indonesian WHV participants who had completed the program and returned to their home country. The findings reveal two overarching themes of work values: (1) values that enhance personal growth, including resilience and self-efficacy, and (2) values related to the pursuit of financial independence. These values contributed to participants’ perceived quality of work life as temporary migrant workers, highlighting the transformative potential of the WHV program beyond economic outcomes